Reengineering of Kuching water board billing process - Wong, Soon Sing (2002)
Reengineering is becoming an increasingly popular option for organizations seeking radical process to bring about dramatic improvement in organizational effectiveness. Recognising the ramifications of BPR, this paper explores the potential of reengineering the billing process of Kuching Water Board.